2021
DOI: 10.1371/journal.pone.0259676
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sex, gender, age, and ethnicity on psychosocial factors and substance use throughout phases of the COVID-19 pandemic

Abstract: Objectives The SARS-CoV-2 (COVID-19) pandemic has had profound physical and mental health effects on populations around the world. Limited empirical research has used a gender-based lens to evaluate the mental health impacts of the pandemic, overlooking the impact of public health measures on marginalized groups, such as women, and the gender diverse community. This study used a gender-based analysis to determine the prevalence of psychosocial symptoms and substance use (alcohol and cannabis use in particular)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 50 publications
(64 reference statements)
8
51
0
1
Order By: Relevance
“…Third, there were not enough studies to attempt subgroup analyses by sociodemographic or other factors, such as professional groups, for example. Cross-sectional studies have reported that there could be differences in mental health by sex or gender that are related to sociodemographic variables (e.g., age, race or ethnicity) and professional roles (e.g., health care workers) 80 , 81 . Cross-sectional analyses, however, do not allow us to determine if any identified associations or differences may have been present prior to the pandemic, and if so, to what degree.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there were not enough studies to attempt subgroup analyses by sociodemographic or other factors, such as professional groups, for example. Cross-sectional studies have reported that there could be differences in mental health by sex or gender that are related to sociodemographic variables (e.g., age, race or ethnicity) and professional roles (e.g., health care workers) 80 , 81 . Cross-sectional analyses, however, do not allow us to determine if any identified associations or differences may have been present prior to the pandemic, and if so, to what degree.…”
Section: Discussionmentioning
confidence: 99%
“…A study using data on hospitalisations, medical visits, and emergency room visits from British Columbia showed that males (but not females) had increased risk of hospitalisation during the pandemic (adjusted risk ratio [aRR] 1.27 [95% CI: 1.17-1.37]), as did those with injection drug use (aRR 2.51 [2.14-2.95]), while women had lower risk of admission unless they were pregnant [30]. Another study from British Columbia showed, inter alia, female sex, Indigenous status, and phase of the pandemic have distinct effects on psychosocial outcomes, with women having more symptoms or more severe symptoms of depression, anxiety, loneliness, and stress than men, regardless of their age or ethnicity [31].…”
Section: Discussionmentioning
confidence: 99%
“…The Patient Health Questionnaire (PHQ-9) was used to measure self-reported symptoms of depression on a Likert scale from zero (not at all) to three (nearly everyday). Scores range from 0–27 with a score of 0–4 indicating minimal depression, 5–14 indicating mild to moderate depression and 15–27 indicating moderately severe to severe depression (Brotto et al, 2021).…”
Section: Methodsmentioning
confidence: 99%